Faktor-faktor yang mempengaruhi efisiensi investasi pada perusahaan sektor pertambangan yang terdaftar di Bursa Efek Indonesia - Rizki Saputra, Maulana; Wicaksono, Ready (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Investment efficiency is the optimal level of investment, the investment is profitable for the company. This study aims to determine the effect of financial statement quality, debt maturity, and accounting conservatism on investment efficiency. The research method applied in this study is a quantitative method. In this study, the sampling technique used purposive sampling as many as 14 mining sector companies listed on the Indonesia Stock Exchange during 2017-2020. The test method used in this research is multiple linear regression analysis. The results of the t-test showed that the quality of financial statements, debt maturity and accounting conservatism had a positive and significant effect on investment efficiency. The results of the F test show that the quality of financial statements, debt maturity and accounting conservatism have a significant effect on investment efficiency.